Association Between COVID-19 Vaccination Status With Severity of Confirmed COVID-19 Patients Period of January-July 2022 in Indonesia - Eka Desi Purwanti; Sudarto Ronoatmojo (Faculty of Public Health, Sriwijaya University, 2023)
The COVID-19 vaccine is known to prevent infection, disease severity, and death from COVID-19. The emergence of a new variant of the SARS-CoV-2 would have an impact on the vaccine's effectiveness. This study aims to examine the association between COVID-19 vaccination status and the severity of COVID-19 symptoms during the dominating period of the Omicron variant. This is a cross-sectional study using secondary data from confirmed COVID-19 patients who were reported in the Ministry of Health's Online Hospital System for the period January-July 2022. Using logistic regression analysis, we calculated the adjusted odds ratio (AOR) of the association between vaccination status and the severity of COVID-19 symptoms. A total of 221,673 confirmed COVID-19 patient data were analyzed. The proportion of patients with severe-critical symptoms is 6.25%. Multivariate analysis showed there was a statistically significant association between COVID-19 vaccination status and the severity of COVID-19 disease with an AOR 0.73 (95% CI 0.65-0.82) in the 1st  dose, 0.38 (95% CI 0.35-0.41) at the 2nd dose, and 0.09 (95% CI 0.07-0.11) at the 3rd dose. But the magnitude of the association in the 2nd and 3rd was lower in the age group >60 years, the group with comorbidities, and the male sex group compared to the younger age group, those without comorbidities, and the female group. It can be concluded that COVID-19 vaccination reduces the risk of severity of COVID-19 disease. Government acceleration efforts and public awareness are needed to immediately increase the coverage of the booster dose of vaccination. Further prospective studies are needed to monitor the effectiveness and duration of vaccine protection as other new variants of the SARS-CoV-2 virus emerge.